2003
DOI: 10.1080/0141192032000057357
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Group‐level Influences on Pupils' Progress in Reading

Abstract: This article investigates the existence or otherwise of group‐level effects on progress in reading. ‘Administrative’ data, i.e. data already produced by a local education authority (LEA) for its own purposes, was combined to give two primary‐age cohorts, each of the order of 2500 pupils, in one medium‐sized LEA in the south‐east of England. After allowing for pupil and global school‐level effects, a wide variety of possible aggregated group‐level effects (AGLEs) was investigated. Different functions of pupil s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
0
16
1
3
Order By: Relevance
“…So what is the way forward? Woodhouse et al (1995), Hutchison (1999) and Browne et al (2001) show how correction for measurement error may be carried out. On a simpler plane, the results in equation 2.3 and 2.4 may be used to estimate the size of any bias in estimated group level coefficients.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…So what is the way forward? Woodhouse et al (1995), Hutchison (1999) and Browne et al (2001) show how correction for measurement error may be carried out. On a simpler plane, the results in equation 2.3 and 2.4 may be used to estimate the size of any bias in estimated group level coefficients.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, Bondi (1991), comparing her results with those of Willms (1986), argued that there was an effect with secondary school children in Scotland, but not with primary. Hutchison (1993) found apparent compositional effects in older primary age pupils in England, but not in younger pupils, though the magnitude of the effects was reduced after allowing for measurement error (Hutchison, 1999(Hutchison, , 2004.…”
Section: Introductionmentioning
confidence: 85%
“…The drop in reported group work may be indicative of teachers losing the ability to apply an effective pedagogical tool in the classroom. This was emphasised by Hutchison (2003) who reported there was a need to ensure that group work was effective in classroom contexts, and concluded that education was not just an activity that takes place in a group, but was a group activity. To have maximum impact it is clear that group work needs to be embedded into the pedagogy and planning in individual curriculum areas and effective CPD provision should be maintained.…”
Section: Resultsmentioning
confidence: 99%
“…Esto fue enfatizado por Hutchison (2003), quien informó sobre la necesidad de asegurar que el aprendizaje entre iguales fuera efectivo en los contextos del aula, y concluyó que la educación no era sólo una actividad que ocurre en el grupo, sino que era una actividad grupal. Para que tenga mayor impacto, está claro que el aprendizaje entre iguales debe ser incorporado dentro de la pedagogía y la planificación de las áreas curriculares individuales.…”
Section: Conclusionesunclassified